2013
DOI: 10.1155/2013/157034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Fabric and Sewing Conditions on Apparel Seam Characteristics

Abstract: Many previous studies showed that seam appearance as well as performance depends on the interrelationship of fabrics, threads, and the stitch/seam selection and lastly on the sewing conditions, which include the needle size, needle thread tension, stitch density, and the appropriate operation and maintenance of the sewing machine. Present investigation elucidates the effect of blend composition, sewing thread size, and sewing needle parameters on garment seam characteristics (i.e., seam strength, seam strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 4 publications
0
46
0
Order By: Relevance
“…Factors aff ecting seam pucker are sewing thread and fabric characteristics, stitch formation, sewing thread tension, fabric feeding and seam type [5]. Seam thread properties, sewing parameters and their compatibility during the sewing have been investigated in several papers [6][7][8][9][10][11][12]. Th e eff ect of sewing parameters on seam pucker was examined most frequently [13,14].…”
Section: Izvlečekmentioning
confidence: 99%
“…Factors aff ecting seam pucker are sewing thread and fabric characteristics, stitch formation, sewing thread tension, fabric feeding and seam type [5]. Seam thread properties, sewing parameters and their compatibility during the sewing have been investigated in several papers [6][7][8][9][10][11][12]. Th e eff ect of sewing parameters on seam pucker was examined most frequently [13,14].…”
Section: Izvlečekmentioning
confidence: 99%
“…The parameters affecting the quality of the threaded seams are the seam strength, its elongation, the seam stiffness when bending, etc. [24][25][26][27].…”
Section: The Aim and Objectives Of Researchmentioning
confidence: 99%
“…Seam durability can be measured through seam efficiency where seam strength is the driving factor [8]. As the standard of any garments is dependent on the quality of seam, the applied seams to make the garments have to fulfill the above mentioned criteria, among which seam strength and appearance of the seams have big importance [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Rengasamy et al [13] and Nayak et al [14] showed the influence of types of sewing thread on the seam efficiency. Impact of linear density of sewing thread has been studied by different researchers [10], [15], [16] and it has been found that the linear density of sewing thread is one of the most influencing factors for the seam strength. Barbulov et al [11] studied the impact of stitch density and of the type of sewing thread on seam strength.…”
Section: Introductionmentioning
confidence: 99%